Recurrent Pseudomembranous Colitis in an Ovarian Cancer Patient Undergoing Carboplatin Chemotherapy - Valerie A. Allen; Kelly J. Manahan; John P. Geisler (Case Reports in Obstetrics and Gynecology)
Background. Diarrhea is a common problem in ovarian cancer patients undergoing chemotherapy and Clostridium difficile infection has been identified as a cause. The proper diagnosis and treatment of diarrhea are critical to patient care, especially to prevent the serious complications from a severe Clostridium difficile infection (CDI). Case. We present a heavily pretreated ovarian cancer patient who developed recurrent pseudomembranous colitis while receiving carboplatin chemotherapy. Despite treatment with oral metronidazole for fourteen days, the patient’s diarrhea relapsed and colonoscopy revealed extensive pseudomembranous colitis. The infection eventually resolved with the combination of oral vancomycin and metronidazole. Conclusions. Diarrhea is a common problem in patients undergoing chemotherapy for ovarian cancer. Management requires obtaining the proper diagnosis. Clostridium difficile associated pseudomembranous colitis must be part of the differential diagnosis. Treatment must be sufficient to prevent relapses of the Clostridium difficile infection to prevent serious consequences in an already vulnerable patient population.